2022
DOI: 10.3389/fonc.2022.906372
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TMEM88 as an Attractive Therapeutic Strategy in Malignant Tumors

Abstract: According to authoritative surveys, the overall morbidity and mortality of malignant tumors show an upward trend, and it is predicted that this trend will not be well contained in the upcoming new period. Since the influencing factors, pathogenesis, and progression characteristics of malignant tumors have not been fully elucidated, the existing treatment strategies, mainly including surgical resection, ablation therapy and chemotherapy, cannot achieve satisfactory results. Therefore, exploring potential therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Involvement of TMEM88 in different malignancies has been reported by different research groups worldwide ( 15 , 16 ). For example, low TMEM88 expression was identified in both thyroid cancer specimens and corresponding cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…Involvement of TMEM88 in different malignancies has been reported by different research groups worldwide ( 15 , 16 ). For example, low TMEM88 expression was identified in both thyroid cancer specimens and corresponding cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…In humans, TMEM88 is involved in cardiomyocyte differentiation and heart development by downregulating the Wnt/β-catenin pathway ( 79 ). In cancer, TMEM88 has been associated with a tumor suppressor and oncogenic function determined by its cellular location ( 25 , 72 ). It was reported that in NSCLC, they identified the expression of TMEM88 in the plasma membrane and in the cytosol.…”
Section: Tmem Proteins With a Dual Function In Different Types Of Cancermentioning
confidence: 99%
“…The overall prognosis for patients with DTC is favorable, while patients with distant metastases have a significantly poorer prognosis [ 7 , 8 ]. The lung is the most commonly affected site of distant metastases for DTC metastases, with an incidence rate of 2–20% [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%